Developmental joint trajectories of anxiety-depressive trait and trait-aggression: implications for co-occurrence of internalizing and externalizing problems. Issue 8 (7th June 2020) - Dugré, Jules R.; Dumais, Alexandre; Dellazizzo, Laura; Potvin, Stéphane
Abstract: Background: In youth, anxiety-depressive traits (ADT) and trait-aggression (TA) are important risk factors of exhibiting maladaptive behaviors in adulthood (i.e. violence and substance use). However, the developmental co-occurrence of these traits in youth remains unknown. We thus sought to investigate the developmental trajectories of ADT and TA within a data-driven approach. The aim was two-fold: (i) to examine the developmental trajectories of ADT and TA in youth from ages 10 to 16, and (ii) to investigate both childhood predictors and problematic outcomes of the identified joint trajectories. Method: The sample comprised 1354 children provided from the Longitudinal Studies of Child Abuse and Neglect (LONGSCAN) Consortium. Group-based trajectory modeling was first employed to identify individual trajectory models of ADT and TA independently (from ages 10 to 16). Then, joint trajectory models were built on the found trajectories. Last, logistic regressions were used to evaluate the childhood characteristics and negative outcomes of the joint trajectory groups. Results: Our results showed five trajectory groups with varying levels of ADT and TA. A significant co-occurrence between ADT and TA was found in three of the trajectory groups. Notably, higher levels of childhood psychopathology and more severe/frequent childhood abuse were found in the groups with moderate to high ADT and high TA. The groups with higher ADT and high TA were also more likely to exhibit violence and substance use. Conclusions: This study exposes the importance of assessing ADT and TA simultaneously and early in childhood to prevent and manage the risk of problematic behaviors in adolescence.